2018
DOI: 10.3389/fphys.2018.01648
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Modulation of Oxidative/Nitrative Stress in Type 4 Cardio-Renal Syndrome and Renal Sarcopenia

Abstract: Chronic kidney disease (CKD) is a public health problem and a recognized risk factor for cardiovascular diseases (CVD). CKD could amplify the progression of chronic heart failure leading to the development of type 4 cardio-renal syndrome (T4CRS). The severity and persistence of heart failure are strongly associated with mortality risk in T4CRS. CKD is also a catabolic state leading to renal sarcopenia which is characterized by the loss of skeletal muscle strength and physical function. Renal sarcopenia also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 161 publications
(276 reference statements)
1
38
0
Order By: Relevance
“…12 Moreover, nitric oxide (NO) deficiency may itself cause oxidative stress. 13 Oxidative stress can lead to endothelial dysfunction through the reduction of the endothelial production of NO, and to structural arterial stiffening through the phenotypic switching of vascular smooth muscle cells (VSMCs), the production of matrix metalloproteinases, and the inhibition of the tissue inhibitors of matrix metalloproteinases. 14 In addition, TNF activates LDL receptor gene transcription, increases alkaline phosphatase protein expression, and reduces a-smooth muscle actin protein expression.…”
Section: From Ckd To Vascular Riskmentioning
confidence: 99%
“…12 Moreover, nitric oxide (NO) deficiency may itself cause oxidative stress. 13 Oxidative stress can lead to endothelial dysfunction through the reduction of the endothelial production of NO, and to structural arterial stiffening through the phenotypic switching of vascular smooth muscle cells (VSMCs), the production of matrix metalloproteinases, and the inhibition of the tissue inhibitors of matrix metalloproteinases. 14 In addition, TNF activates LDL receptor gene transcription, increases alkaline phosphatase protein expression, and reduces a-smooth muscle actin protein expression.…”
Section: From Ckd To Vascular Riskmentioning
confidence: 99%
“…Various oxidation products have been shown to be overabundant in CKD. Increased ROS production has been reported to contribute to myocardial hypertrophy and fibrosis by lipid peroxidation, proinflammatory cytokines and DNA damage [35,36]. A marker of oxidative stress, 8-isoprostane, increases as CKD progresses [37].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Yuan et al found that accumulation of truncal fat mass was associated with elevated levels of circulating hepatic growth factor (HGF), a marker for obesity in the general population, and in the presence of protein-energy wasting predicted higher mortality [127]. Other underlying mechanisms remain unknown, although some phenomena are partially explained by altered mineral metabolism, sustained inflammation, elevated oxidative/nitrative stress [128], malnutrition, and accumulated uremic toxins [122,123,124,129,130]. Recently, Jheng et al focused on ER stress in this context and clarified that uremic toxin not only promotes expression of E3 ubiquitin ligases, but also stimulates eIF2α phosphorylation and XBP1 mRNA splicing in the UPR [125].…”
Section: Lipotoxicity In Skeletal Muscle: Perspectives In Diabetesmentioning
confidence: 99%